Validity and Inter-Device Reliability of the OTBeat BurnTM Monitor to Estimate Heart Rate During Exercise - Matteo F. de Leon; Clayton L. Camic; Matthew J. Herring; Christopher M. Hill (Sports)
The purpose of this study was to determine the accuracy and inter-device reliability of the OTBeat BurnTM heart rate monitor during an incremental test to exhaustion on a cycle ergometer. Twenty males (mean ± SD age = 21.1 ± 1.9 years) volunteered to complete a test to exhaustion on a cycle ergometer with OTBeat BurnTM devices placed on the forearm and upper arm, with a 12-lead electrocardiogram used as the criterion. The heart rate was recorded every 30 s and averaged across each two-minute stage. Accuracy was assessed through calculation of the mean absolute percent error (MAPE), Bland–Altman plot, and Lin’s concordance correlation coefficient (CCC). An intraclass correlation coefficient (ICC) was used to assess the inter-device reliability. Statistical significance was set at α < 0.05. The MAPE (±SD), Bland–Altman regression analyses, and Lin’s CCC values were 0.9 (±0.6)% and 0.8 (±0.5)%, r = 0.107 and 0.303, and rc = 0.998 and 0.998 for the forearm and the upper arm monitors, respectively. The ICC for inter-device reliability was R = 0.999. Our findings indicated the OTBeat BurnTM monitors placed on the forearm and upper arm provided highly accurate and reliable values when compared to an electrocardiogram from low to maximal exercise intensities.